The value of compassionate support to address smoking: A qualitative study with people who experience severe mental illness - McCarter, Kristen; McKinlay, Melissa L.; Cocks, Nadine; Brasier, Catherine; Hayes, Laura; Baker, Amanda L.; Castle, David; Borland, Ron; Bonevski, Billie; Segan, Catherine; Kelly, Peter J.; Turner, Alyna; et al. (Frontiers in Psychiatry, 2022)
Introduction People experiencing severe mental illness (SMI) smoke at much higher rates than the general population and require additional support. Engagement with existing evidence-based interventions such as quitlines and nicotine replacement therapy (NRT) may be improved by mental health peer worker involvement and tailored support. This paper reports on a qualitative study nested within a peer researcher-facilitated tobacco treatment trial that included brief advice plus, for those in the intervention group, tailored quitline callback counselling and combination NRT. It contextualises participant life experience and reflection on trial participation and offers insights for future interventions. Methods Qualitative semi-structured interviews were conducted with 29 participants in a randomised controlled trial (intervention group n = 15, control group n = 14) following their 2-month (post recruitment) follow-up assessments, which marked the end of the ‘Quitlink’ intervention for those in the intervention group. Interviews explored the experience of getting help to address smoking (before and during the trial), perceptions of main trial components including assistance from peer researchers and tailored quitline counselling, the role of NRT, and other support received. A general inductive approach to analysis was applied. Results We identified four main themes: 1) the long and complex journey of quitting smoking in the context of disrupted lives; 2) factors affecting quitting (desire to quit, psychological and social barriers, and facilitators and reasons for quitting); 3) the perceived benefits of a tailored approach for people with mental ill-health including the invitation to quit and practical resources; and 4) the importance of compassionate delivery of support, beginning with the peer researchers and extended by quitline counsellors for intervention participants. Subthemes were identified within each of these overarching main themes. Discussion The findings underscore the enormity of the challenges that our targeted population face and the considerations needed for providing tobacco treatment to people who experience SMI. The data suggest that a tailored tobacco treatment intervention has the potential to assist people on a journey to quitting, and that compassionate support encapsulating a recovery-oriented approach is highly valued.